Theology, Christian spirituality and the Lord’s prayer according to the Gospel of Matthew - van der Merwe, Dirk G. (In die skriflig : tydskrif van die Gereformeerde Teologiese Vereniging, 2026)
Prayer facilitates and constitutes dialogue between God and Christians. It also enables believers to experience God in prayer. A prerequisite is the recognition that God is the bona fide source of daily provision and the supreme One who brings about spiritual transformation and maturity. The objective of this research was to explore how the Lord’s Prayer offers the principal spiritual directives that guide Christians towards spiritual growth and enable them to experience divine involvement. Therefore, methodologically, the Lord’s Prayer has been examined from a theological-metaphorical perspective to discern the divine lived experiences embedded in the text. Consequently, the approach involved, firstly, a discussion of the character or nature of prayer among Christians; secondly, the contextualisation of the Lord’s Prayer within Matthew; thirdly, the localisation of the Prayer within the Sermon on the Mount and the Gospel; and finally, an investigation of the spirituality conveyed through the Prayer from a theological-metaphorical perspective. The significance of this study lies in alerting Christian believers to God’s presence and involvement in their daily lives and experience this divine presence and involvement more deeply. Insight into the various petitions of the Lord’s Prayer equips believers to experience God within the different dimensions Jesus addresses in the petitions in the Prayer. Thus, every prayer has the potential to foster a personal divine lived experience with God – whether in the ‘glorification of God’s name’, in effecting the ‘coming of the kingdom’, and in living according to ‘the will of God’. Contribution: Prayer creates a sacred space where God’s voice addresses the pray-er and provides corresponding circumstances. This study provides a foundation for Systematic Theology, New Testament studies, Practical Theology, and Christian ethics in post-modern contexts. The theology embedded in prayer is here interpreted metaphorically as a means of understanding divine spirituality.